2018
DOI: 10.1002/ccr3.1476
|View full text |Cite
|
Sign up to set email alerts
|

Partial cystectomy for a primary locally advanced leiomyosarcoma of the bladder: a case report and review of the literature

Abstract: Key Clinical MessagePartial cystectomy with wide local excision may be considered a suitable option for selective cases of locally advanced bladder leiomyosarcoma without evidence of distant metastasis; thereby preserving the functional outcome and quality of life. A negative margin, complete tumor resection, and frequent follow‐up in such patients are mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
(28 reference statements)
0
6
0
3
Order By: Relevance
“…Recently, more cases of young patients with NUBC have been treated with partial cystectomy. However, they are restricted to a few case reports and series [4]. We reported our experience on partial cystectomy for NUBC which showed variable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more cases of young patients with NUBC have been treated with partial cystectomy. However, they are restricted to a few case reports and series [4]. We reported our experience on partial cystectomy for NUBC which showed variable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of non-urothelial tumours are considerably higher (8%) compared to India and Pakistan 3-4% [10,11]. Such non-urothelial bladder cancers are aggressive in nature and associated with poor survival [19][20][21]. Although the reason remains unclear, Sasikumar et al has suggested that the common use of agrochemicals and pesticides used in the semiurban and the rural community may be a possible explanation [9].…”
Section: Discussionmentioning
confidence: 99%
“…A indicação mais comum desse procedimento é um tumor vesical músculo-invasivo (T2 ou mais) sem evidência de metástases a distância 13 . Geralmente, inclui ressecção de margens livres de invasão tumoral de cerca de dois e três centímetros e é acompanhada de radioterapia e quimioterapia adjuvantes 14 .…”
Section: Relato De Casounclassified
“…A cistectomia parcial é considerada um procedimento alternativo à cistectomia radical, já que apresenta como benefício a preservação funcional da bexiga e uma menor morbidade ao paciente 14 . É geralmente indicada para pacientes jovens com tumores de pequena dimensão.…”
Section: Relato De Casounclassified
See 1 more Smart Citation